KESIAPAN GURU MATEMATIKA DALAM MENYONGSONG MASYARAKAT EKONOMI ASEAN (MEA) - Rangkuti, Ahmad Nizar (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
Education has an important role in building human resource competitive and able to compete with other countries. Therefore, to meet MEA, education should be able to prepare skilled human resource (HR), sensitive and critical in facing the challenges and changes that will occur in the education world. In order, math teachers in ready for MEA, math teachers must understand the strategic issues, professional development of teachers, and the revitzlization of the learning of mathematics.